2020
DOI: 10.3390/ijms21051747
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ Agonism Upregulates Forkhead Box A2 to Reduce Inflammation in C2C12 Myoblasts and in Skeletal Muscle

Abstract: Daily activities expose muscles to innumerable impacts, causing accumulated tissue damage and inflammation that impairs muscle recovery and function, yet the mechanism modulating the inflammatory response in muscles remains unclear. Our study suggests that Forkhead box A2 (FoxA2), a pioneer transcription factor, has a predominant role in the inflammatory response during skeletal muscle injury. FoxA2 expression in skeletal muscle is upregulated by fatty acids and peroxisome proliferator-activated receptors (PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…Another mediator of cytokine homeostasis [45], foxA2, was upregulated following benzene exposure in our study. FoxA2 expression can also be upregulated by fatty acids and peroxisome proliferator-activated receptors in skeletal muscle in the mice model [45]. Nfkbia is another detoxification gene that is also involved with inflammatory response.…”
Section: Discussionsupporting
confidence: 59%
“…Another mediator of cytokine homeostasis [45], foxA2, was upregulated following benzene exposure in our study. FoxA2 expression can also be upregulated by fatty acids and peroxisome proliferator-activated receptors in skeletal muscle in the mice model [45]. Nfkbia is another detoxification gene that is also involved with inflammatory response.…”
Section: Discussionsupporting
confidence: 59%
“…The results showed that the proliferation of C2C12 cells was significantly inhibited, and the cellular IL-1β and IL-18 were highly expressed. Studies have indicated that the NO antagonist L-NAME promotes the expression of C2C12 cell antigen, while SNP has the opposite effect, suggesting that NO may be involved in the downregulation of skeletal muscle inflammation (Frost et al, 2004;Boyd et al, 2006;Kumar et al, 2017;He et al, 2018;Phua et al, 2020). The apoptosis and inflammation related proteins ASC, caspase 1, and NLRP3 were detected by qRT-PCR and western blotting after L-NAME and SNP, respectively, in the C2C12 supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we predicted transcription factors at the CRY2-P7 locus and found that the FOXA2 transcription factor can specifically bind to the II genotype sequence. FOXA2 contributes to homeostasis in skeletal muscle and is essential for both estrogen and androgen transmission [33]. The PIC value of a marker is equivalent to its ability to detect polymorphisms between individuals in a population and is an indicator of the marker quality in genetic studies; the higher this ability, the greater its value [34].…”
Section: Discussionmentioning
confidence: 99%